Quality Improvement and Personalization for Statins: the QUIPS Quality Improvement Randomized Trial of Veterans’ Primary Care Statin Use - B Sussman, Jeremy (J Gen Intern Med, 2018)
BACKGROUND: Implementation of new practice guidelines for statin use was very poor. OBJECTIVE: To test a multi-component quality improvement intervention to encourage use of new guidelines for statin use. DESIGN: Cluster-randomized, usual-care controlled trial. PARTICIPANTS: The study population was primary care visits for patients who were recommended statins by the 2013 guidelines, but were not receiving them. We excluded patients who were over 75 years old, or had an ICD9 or ICD10 code for end-stage renal disease, muscle pain, pregnancy, or in vitro fertilization in the 2 years prior to the study visit. INTERVENTIONS: A novel quality improvement intervention consisting of a personalized decision support tool, an educational program, a performance measure, and an audit and feedback system. Randomization was at the level of the primary care team. MAIN MEASURES: Our primary outcome was prescription of a medium- or high-strength statin. We studied how receiving the intervention changed care during the quality improvement intervention compared to before it and if that change continued after the intervention. KEY RESULTS: Among 3787 visits to 43 primary care providers, being in the intervention arm tripled the odds of patients being prescribed an appropriate statin (OR 3.0, 95% CI 1.8–4.9), though the effect resolved after the personalized decision support ended (OR 1.7, 95% CI 0.99–2.77). CONCLUSIONS: A simple, personalized quality improvement intervention is promising for enabling the adoption of new guidelines. CLINICALTRIALS.GOV IDENTIFIER: NCT02820870 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-018-4681-6) contains supplementary material, which is available to authorized users.